An elliptical-shaped rectangular slot antenna at 2.48 GHz for hyperthermia application - Khan A.; Dubey S.K.; Singh A.K. (My University, 2025)
In this paper, a novel integrated elliptical ringtone antenna has been proposed. The proposed antenna operates in the industrial, scientific and medical band and the overall size of the antenna is 128 × 128 × 1.58 mm3. The antenna provides a valid specific absorption rate input profile and displays better performance at 2.48 GHz. Simulation of the proposed structure was done on FEM-based high frequency structure simulator 2020R1 software and validated by measured results. © 2023 Wiley Periodicals LLC.